3-D Viscous Flow Analysis of a Mixed Flow Pump Impeller. (2001) - Miner Miner, Steven M. Steven M.
Abstract : This paper presents the results of a study using a coarse grid to analyze the flow in the impeller of a mixed flow pump. A commercial computational fluid dynamics code (FLOTRAN) is used to solve the 3-D Reynolds Averaged Navier Stokes equations in a rotating cylindrical coordinate system. The standardk - ε turbulence model is used. The mesh for this study uses 26, 000 nodes and the model is run on a SPARCstation 20. This is in contrast to typical analyses using in excess of 100, 000 nodes that are run on a super computer platform. The smaller mesh size has advantages in the design environment. Stage design parameters are, rotational speed 1185 rpm, flow coefficientφ = 0.116, head coefficientψ = 0.094, and specific speed 2.01 (5475 US). Results for the model include circumferentially averaged results at the leading and trailing edges of the impeller, and analysis of the flow field within the impeller passage. Circumferentially averaged results include axial and tangential velocities, static pressure, and total pressure. Within the impeller passage the static pressure and velocity results are presented on surfaces from the leading edge to the trailing edge, the hub to the shroud, and the pressure surface to the suction surface. Results of this study are consistent with the expected flow characteristics of mixed flow impellers, indicating that small CFD models can be used to evaluate impeller performance in the design environment.